2011
DOI: 10.1039/c1cc15451f
|View full text |Cite
|
Sign up to set email alerts
|

The hydrazide/hydrazone click reaction as a biomolecule labeling strategy for M(CO)3 (M = Re, 99mTc) radiopharmaceuticals

Abstract: Facile reactivity of hydrazides and aldehydes was explored as potential coupling partners for incorporation into M(CO)3 (M = Re, 99mTc) based radiopharmaceuticals. Both ‘click, then chelate’ and ‘prelabel, then click’ synthetic routes produced identical products in high yields and lacked metal-hydrazide/-hydrazone interactions, highlighting the potential of this click strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 20 publications
1
32
0
1
Order By: Relevance
“…IR analysis showed the expected v CO stretching bands for the fac -[Re I (CO) 3 ] + core (2028 and 1903 cm −1 ) as well as the presence of the isothiocyanate group (2107 cm −1 ), and ESI-MS analysis was consistent with the desired complex (583.1 m / z ). While the NMR spectra of 5 showed singlets for the methylene protons of the DPA chelate as opposed to AB quartets seen with several other fac -[M I (CO) 3 (DPA)] complexes, 5,17 the downfield shifts of these protons in 5 (4.88 ppm) compared to the original ligand (3.79 ppm) indicated that metal complexation occurred at the DPA portion of the chelate as expected.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…IR analysis showed the expected v CO stretching bands for the fac -[Re I (CO) 3 ] + core (2028 and 1903 cm −1 ) as well as the presence of the isothiocyanate group (2107 cm −1 ), and ESI-MS analysis was consistent with the desired complex (583.1 m / z ). While the NMR spectra of 5 showed singlets for the methylene protons of the DPA chelate as opposed to AB quartets seen with several other fac -[M I (CO) 3 (DPA)] complexes, 5,17 the downfield shifts of these protons in 5 (4.88 ppm) compared to the original ligand (3.79 ppm) indicated that metal complexation occurred at the DPA portion of the chelate as expected.…”
Section: Resultsmentioning
confidence: 65%
“…813 Among these reactions, isoxazole formation, 14 thioether formation, 15,16 and hydrazone generation have been successfully utilized in proof-of-concept studies with the fac -[M I (CO) 3 ] + core. 17 …”
Section: Introductionmentioning
confidence: 99%
“…In fact, they have been used as drug carriers, dermal fillers, detergents, and wound-healing supports. [29][30][31] Amongm any newly developed chemoselective ligations, [32][33][34] click reactions such as the copper-mediated 1,3-dipolar Huisgenc ycloaddition, [35,36] andh ydrazone formation relying on carbonyl functionality [7,37] have seen widespread use. [29][30][31] Amongm any newly developed chemoselective ligations, [32][33][34] click reactions such as the copper-mediated 1,3-dipolar Huisgenc ycloaddition, [35,36] andh ydrazone formation relying on carbonyl functionality [7,37] have seen widespread use.…”
Section: Concepts Of Difunctionalization Of Polysaccharides and Hydromentioning
confidence: 99%
“…In principle,t he chemistry chosen should allow either of the two functional groups (aldehyde and hydrazide) to be introduced into any of the chosen polysaccharides.F urthermore, ab iologically relevant ligand (L), namely, cRGDfK (7), was plan-ned to be attachedt ot he polysaccharide strand by utilizing as econd click reaction. The first reaction between two clickable strands provides hydrogels, and the second reaction introduces the biologically relevant ligand.…”
Section: Introductionmentioning
confidence: 99%
“…PAH has been utilized to create stimuli-responsive hydrogels, 21 drug delivery systems, 22,23 ion exchange resins, 21 and glycopolymers. 24 The hydrazide moiety located along the backbone of the polymer is an effective conjugation site for many types of aldehyde-containing molecules, induding sugars with a reducing end.…”
Section: Introductionmentioning
confidence: 99%